An assessment of knowledge and factors that expose young female student nurses to HIV infection at University of Namibia’s - Uushona, Selma Ingandipewa (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.